A preliminary study on the treatment of human blood soiled stubs, in presence of GSR particles. (June 2022) - Rotter, Gabriele; Pazzi, Marco; Mattutino, Grazia
Abstract: In the investigation of gunshot deaths, Bloodstains Pattern Analysis (BPA) and, in particular, backspatter patterns found on the body of the suspect/victim and on the surfaces close to the entrance wound of the bullet can provide investigators with important indications on the dynamics of the events. Backspatter patterns have, however, morphological characteristics common to other bloodstains of different origin, so, in order to positively identify them, a possible solution is represented by their sampling, using an aluminum stub for electron microscopy, for the detection of gunshot residues (GSR) present. The latter, however, if present below the small blood crusts, could be difficult to detect during analysis by Scanning Electron Microscopy/Energy Dispersive X-ray microanalysis (SEM/EDX). In this preliminary study we propose the treatment of the stub surface with a solution based on sodium hypochlorite and calcium chloride, in order to remove/reduce the blood crusts present on the stub surface. Highlights: Bloodstain Pattern Analysis is useful for the reconstruction of the crime dynamics. Backspatter Patterns are critical for discriminating suicides from homicides. Blood crusts, sampled with a stub, can occult GSR particles. Treatment of the stub is proposed to remove/reduce blood crusts. After treatment, GSRs previously occulted by blood can be detected.